2021
DOI: 10.3390/jcm10215120
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Work-Up of the Aortic Patient: An Integrated Approach toward the Best Therapeutic Option

Abstract: Aortic stenosis (AS) is the most common valvular heart disease. In the last decade, transcatheter aortic valve implantation (TAVI) has become the standard of care for symptomatic patients at high surgical risk. Recently, indications to TAVI have also been extended to the low surgical risk and intermediate surgical risk populations. Consequently, in this setting, some aspects acquire greater relevance: surgical risk evaluation, clinical assessment, multimodality imaging of the valve, and management of coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 117 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…Similarly, our present study showed LEAD to be an independent risk factor for CVD and HF episodes following aortic valve intervention. In summary, the Heart Team is at the center of the decision-making process in patients with DAS [31][32][33]. The gathered experience indicates that a multidimensional and multidisciplinary pre-procedural work-up in patients with severe DAS, including a thorough assessment of coexisting disorders, results in an optimal treatment strategy and can be associated with a superior prognosis when compared to conservative medical management [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our present study showed LEAD to be an independent risk factor for CVD and HF episodes following aortic valve intervention. In summary, the Heart Team is at the center of the decision-making process in patients with DAS [31][32][33]. The gathered experience indicates that a multidimensional and multidisciplinary pre-procedural work-up in patients with severe DAS, including a thorough assessment of coexisting disorders, results in an optimal treatment strategy and can be associated with a superior prognosis when compared to conservative medical management [31][32][33].…”
Section: Discussionmentioning
confidence: 99%